(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: The infection of HIV from mother to child can be prevented through the prevention of transmission from mother to child’s efforts based on the WHO recommendation in 2010. The cadres are considered to be capable of monitoring pregnant women in their area, so they are considered to be capable of moving pregnant woman’s willingness to carry out an HIV test at the nearest Community Health Center or Puskesmas. The purpose of this study was to prove the influence of training given to cadres toward predisposing factors of PITC of HIV Services on Pregnant Women and influence of the training and PITC of HIV Service utilization by the pregnant women after 1-3 months follow up period. Method: This quasi experimental research conducted from March to May 2019. The population was posyandu cadres. Sampling was 42 cadres, divided into treatment and control group. Data assessed using a questionnaire on the pre-test and post-test. The Results: A significant difference in knowledge showed after the training between treatment and control group p=0.000. On the contrary, no significant difference in self-efficacy shown before and after the training in the treatment and control group p = 0.178 and 0.216, consecutively. There was also no significant influence showed on the attitude of cadres before and after the training for the treatment and control group p=0.488 and p=0.731, consecutively. There was a significant influence of training toward the PITC of HIV service utilization by the pregnant women p=0.004. Conclusion: There was a significant influence between training toward knowledge of the posyandu cadres’ knowledge on the PITC of HIV and the PITC of HIV service utilization by the pregnant women.